A fluorogenic probe for granzyme B enables in-biopsy evaluation and screening of response to anticancer immunotherapies - Scott, Jamie I.; Mendive-Tapia, Lorena; Gordon, Doireann; Barth, Nicole D.; Thompson, Emily J.; Cheng, Zhiming; Taggart, David; Kitamura, Takanori; Bravo-Blas, Alberto; Roberts, Edward W.; Juarez-Jimenez, Jordi; Michel, Julien; et al. (Nature communications, 2022)
Immunotherapy promotes the attack of cancer cells by the immune system; however, it is difficult to detect early responses before changes in tumor size occur. Here, we report the rational design of a fluorogenic peptide able to detect picomolar concentrations of active granzyme B as a biomarker of immune-mediated anticancer action. Through a series of chemical iterations and molecular dynamics simulations, we synthesize a library of FRET peptides and identify probe H5 with an optimal fit into granzyme B. We demonstrate that probe H5 enables the real-time detection of T cell-mediated anticancer activity in mouse tumors and in tumors from lung cancer patients. Furthermore, we show image-based phenotypic screens, which reveal that the AKT kinase inhibitor AZD5363 shows immune-mediated anticancer activity. The reactivity of probe H5 may enable the monitoring of early responses to anticancer treatments using tissue biopsies. Granzyme B is found in activated T cells and can be used as a marker of T cell activation. Here, the authors generate a fluorescent probe that can detect Granzyme B levels in tumours, and has the potential to be used as a biomarker of response to immunotherapy.